Determinan Perilaku Pengelolaan Keuangan pada UMKM di Kabupaten Kediri - Larasaty, Faradila; Makaryanawati, Makaryanawati; Furqorina, Rizka (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p05, 2021)
This study aims to determine the effect of financial knowledge, financial planning and self-control on MSME's financial management behavior. The sampling technique in this study uses convenience sampling method. Data collected using questionnaire. This research used a quantitative approach and the analytical method used multiple linear regression. The results of this study are financial knowledge and financial planning have a positive effect on MSME's financial management behavior. Self control has no significant effect on the financial management behavior of SMEs. Based on the results of the study, the average respondent has good financial knowledge and has carried out financial planning well so there is good financial management behavior. Keywords: Financial Knowledge; Financial Planning; Self Control; MSME`s Financial Management.